Angiomatous Meningioma in the Craniocervical Junction - Shunsuke Ito; Yoichi Iizuka; Masanori Aihara; Hiromi Koshi; Tokue Mieda; Eiji Takasawa; Sho Ishiwata; Yusuke Tomomatsu; Akira Honda; Kazuhiro Inomata; Hirotaka Chikuda (Case Reports in Orthopedics)
Introduction. Spinal angiomatous meningioma arising in the craniocervical junction has not been reported. Case Presentation. A 68-year-old man presented to our hospital with pain in the back and left leg. He showed slight motor weakness in his upper extremities. Magnetic resonance imaging revealed a mass with marked enhancement in the craniocervical junction. Computed tomography angiography showed feeding vessels arising from the right vertebral artery. Preoperative embolization of the feeding vessels was performed to reduce intraoperative bleeding. Gross total resection of the tumor was achieved by debulking and piecemeal resection. The tumor attachment to the dura mater was also resected (Simpson grade 1 resection). A histopathological examination confirmed the diagnosis of an angiomatous meningioma. The patient’s symptoms improved shortly after surgery. Conclusions. We achieved gross total resection of spinal angiomatous meningioma arising in the craniocervical junction. A preoperative evaluation and embolization of the feeding arteries may help prevent massive intraoperative bleeding.